Jasmonate Zim-Domain Protein 9 Interacts With Slender Rice 1 to Mediate the Antagonistic Interaction Between Jasmonic and Gibberellic Acid Signals in Rice - Um, Tae Young; Lee, Han Yong; Lee, Sangyool; Chang, Sun Hyun; Chung, Pil Joong; Oh, Ki-Bong; Kim, Ju-Kon; Jang, Geupil; Choi, Yang Do (Frontiers in Plant Science, 2018)
The jasmonic acid (JA) and gibberellic acid (GA) signaling pathways interact to coordinate stress responses and developmental processes. This coordination affects plant growth and yield, and is mediated by interactions between the repressors of each pathway, the JASMONATE ZIM-DOMAIN PROTEIN (JAZ) and DELLA proteins. In this study we attempted to identify rice (Oryza sativa) JAZs that interact with rice DELLAs such as SLENDER RICE 1 (SLR1). Analysis of protein–protein interactions showed that OsJAZ8 and OsJAZ9 interact with SLR1; OsJAZ9 also interacted with the SLR1-LIKE (SLRL) protein SLRL2. Based on this broader interaction, we explored the function of OsJAZ9 in JA and GA responses by analyzing transcript levels of the JA-responsive gene OsbHLH148 and the GA-responsive gene OsPIL14 in OsJAZ9-overexpressing (OsJAZ9-Ox) and osjaz9 mutant plants. OsbHLH148 and OsPIL14 encode key transcription factors controlling JA and GA responses, respectively, and JA and GA antagonistically regulate their expression. In OsJAZ9-Ox, the expression of OsbHLH148 was downregulated and the expression of OsPIL14 was upregulated. By contrast, in osjaz9 mutants, the expression of OsbHLH148 was upregulated and the expression of OsPIL14 was downregulated. These observations indicated that OsJAZ9 regulates both JA and GA responses in rice, and this finding was supported by the opposite expression patterns of OsDREB1s, downstream targets of OsbHLH148 and OsPIL14, in the OsJAZ9-Ox and osjaz9 plants. Together, these findings indicate that OsJAZ9 suppresses JA responses and promotes GA responses in rice, and the protein–protein interaction between OsJAZ9 and SLR1 is involved in the antagonistic interplay between JA and GA.